Pengaruh Pemanfaatan Media Pembelajaran oleh Guru terhadap Aktivitas Siswa dalam Pembelajaran Ilmu Pengetahuan Sosial (IPS) Terpadu pada Siswa Kelas VIII Madrasah Tsanawiyah Diniyah Puteri Pekanbaru - Risti Liana (Economica, 2017)
The purpose of this study is whether there is significant effect between utilizing teaching media toward students activities in the study of integrated social studies. The subject in this research is the teacher of social studies and eighth year of Madrasah Tasanawiyah Diniyah Puteri Pekanbaru, while the object is the influence of utilizing teaching media toward students activities in the study of integrated social studies. The populations in this research are all eighth year of as much as 42 persons and a teacher of social studies, because the populations in this research are very little so the writer doesn’t take any samples therefore this research is called by polulation reserach. The data in this research are taken throught some techniques they are questionnaires and documentation. The data which have been collected are interval data and then those data are analyzed by using product moment correlation technique.Finnaly, the conclusion of this study is there is significant influence between utilizing teaching media by the teacher toward students activities in the study of integrated social studies by knowing that rxy = 0,479 is bigger than “r” table on significant level of 5% and 1% it is 0,304<0,479>0,393.